If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
x = 0
x^2 = 0
x = 0
x = 0
x^2 = 0
x^2 = 0
1*x^2 = 0 // : 1
x^2 = 0
x = 0
x in (-oo:0) U (0:+oo)
3/(x^2)-(7/x)-9-3 = 3-4/x // - 3-4/x
3/(x^2)-(7/x)-(-4/x)-9-3-3 = 0
4*x^-1-7*x^-1+3/(x^2)-9-3-3 = 0
3*x^-2-3*x^-1-15 = 0
t_1 = x^-1
3*t_1^2-3*t_1^1-15 = 0
3*t_1^2-3*t_1-15 = 0
DELTA = (-3)^2-(-15*3*4)
DELTA = 189
DELTA > 0
t_1 = (189^(1/2)+3)/(2*3) or t_1 = (3-189^(1/2))/(2*3)
t_1 = (3*21^(1/2)+3)/6 or t_1 = (3-3*21^(1/2))/6
t_1 = (3-3*21^(1/2))/6
x^-1-((3-3*21^(1/2))/6) = 0
1*x^-1 = (3-3*21^(1/2))/6 // : 1
x^-1 = (3-3*21^(1/2))/6
-1 < 0
1/(x^1) = (3-3*21^(1/2))/6 // * x^1
1 = ((3-3*21^(1/2))/6)*x^1 // : (3-3*21^(1/2))/6
6*(3-3*21^(1/2))^-1 = x^1
x = 6*(3-3*21^(1/2))^-1
t_1 = (3*21^(1/2)+3)/6
x^-1-((3*21^(1/2)+3)/6) = 0
1*x^-1 = (3*21^(1/2)+3)/6 // : 1
x^-1 = (3*21^(1/2)+3)/6
-1 < 0
1/(x^1) = (3*21^(1/2)+3)/6 // * x^1
1 = ((3*21^(1/2)+3)/6)*x^1 // : (3*21^(1/2)+3)/6
6*(3*21^(1/2)+3)^-1 = x^1
x = 6*(3*21^(1/2)+3)^-1
x in { 6*(3-3*21^(1/2))^-1, 6*(3*21^(1/2)+3)^-1 }
| y-3y-8/8/35/24+7/3y | | y-8=-2/11(x+12) | | 9t-22=50+t | | (p+12)+(2p-23)+p=669 | | 2a+6a=a | | 1/4-l+3/6+l=0 | | 1-3/7x | | (x+7)/14 | | 6x^3-3x^2+24x+5=0 | | 2x-18=38+9x | | 0=-2x^2+9x+9 | | -b/c+5=d | | -b/3+5=d | | x^2-4.25x+2=0 | | x^2-8.5x+2=0 | | c=100+.8(y-(60+.25y)) | | -1c+6=3c-9 | | 5w+8=3w-6 | | (1/4a)=23 | | 5+16z-4=7z+66-4z | | r^2=14-5r | | x+(7/5)x=84 | | x+(7/5)x=96 | | 15(t-2)+3t=6(3t+3)-11 | | -5x-15=5 | | 2x+2x-7=17 | | 2(t+4)=3(x-2) | | y^4-32y^2-400=0 | | 3x/5-2=-4/5 | | -1/-2y-(y+1/4)=1/64(y-6) | | 15+.25x=20+.05x | | 4y^4-32y^2-400=0 |